Gamer and Non-gamer Students in Listening Skills: A Comparative Study of Third Semester Students in Academic Year 2023/2024 - Alfian, Ali; Amin, Muhammad; Lestari, Yuni Budi (Program Studi Pendidikan Bahasa Inggris, 2024)
This study aims to reveal if there are significant differences in extensive listening skills between gamer and non-gamer of 3rd-semester students at the University of Mataram. The subject of the study involves the 3rd-semester students in the English department of Mataram University which consists of 10 students in total, by using a questionnaire to divide between gamer and non-gamer students, the researcher found that 5 of them are gamers and 5 others are non-gamers. After dividing the students into two groups, they were given TOEIC listening tests to check their listening scores, and the data collected were checked using the independent sample t-test scaling method. From the result of the analysis, it was found that the critical t-value is 2.306 which is smaller than the t-value which is 3.952. Therefore the null hypothesis is rejected which means there are significant differences between gamer and non-gamer of 3rd-semester students at the University of Mataram.